Perspectives on the study of work-life balance in relation redesign approaches of job among banking professionals: Antecedents and outcomes - Ahamed S B, Inayath; Elango, Dinesh (Journal of Management, Economics, and Industrial Organization, 2021)
This novel study examines the relation of work-life balance with different job resigning approaches. The core objective of this study is to explore the impact of job enlargement, job rotation and job enrichment on the work-life balance of banking professionals. A structured questionnaire used for collecting data from top management of banking professionals. The sample size is 300 and out of 300 samples, 259 (86.3%) had responded about their experiences towards redesign approaches with work-life balance. The work-life balance considered as a dependent variable and job enlargement, job rotation and job enrichment is taken as independent variables. The multiple regression model used to analyze and explore the significant relation between work-life balances and job enlargement, job rotation and job enrichment. The findings of the study established that there is a positive correlation between two approaches of job resign namely job enrichment and job enlargement and work-life balance and a negative correlation between job rotation and work-life balance.
Keywords: job enlargement; job enrichment; job rotation; work-life balance; banking sector